PENEGAKAN HUKUM TERHADAP PELAKU YANG MELAKUKAN TINDAK PIDANA PEMERASAN DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Lisda Desiana; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
Extortion is an action that often occurs in people's daily life activities, extortioncan occur with various backgrounds and certain motives. Extortion in Dutch apersingand in English is called blackmail is a common crime. The word extortion in Indonesiancomes from the root word